Encorafenib in combination with binimetinib for unresectable or metastatic melanoma with BRAF mutations. Issue 3 (4th March 2019) - Trojaniello, Claudia; Festino, Lucia; Vanella, Vito; Ascierto, Paolo A.
ABSTRACT: Introduction: Combination treatment with a BRAF inhibitor and MEK inhibitor is the standard of care for patients with advanced BRAF V600 mutation-positive melanoma. With the currently available combinations of dabrafenib plus trametinib and vemurafenib plus cobimetinib, median progression-free survival (PFS) of over 12 months has been achieved. However, treatment resistance and disease recurrence remain a clinical challenge. Areas covered: Encorafenib in combination with bimetinib offers a new approach that may offer benefits over existing BRAF/MEK inhibitor combinations. Expert opinion: While other BRAF/MEK inhibitor combinations have achieved a median overall survival (OS) of 22 months, patients with advanced BRAF mutation-positive melanoma treated with encorafenib plus binimetinib achieved a median OS of 33.6 months in the phase III COLUMBUS trial. PFS also appears to be improved with encorafenib plus binimetinib. This improved efficacy may be related to the distinct pharmacokinetics of encorafenib, with prolonged binding to the target molecule providing greater BRAF inhibition and increased potency compared with other drugs in the same class. Increased specificity of encorafenib may also result in better tolerability with less off-target effects, including reduced occurrence of pyrexia and photosensitivity. Encorafenib plus binimetinib seems likely to emerge as a valuable therapeutic alternative to established BRAF/MEK inhibitor combinations.